Effect of seed priming on enhancement of seed vigor, seedling growth and enzyme activities in accelerated aged seeds of four Sainfoin species - Azadeh kavandi; علی اشرف جعفری; Amir Ghorbankhani; Fereshta shahbazi Asl (علوم و فناوری بذر ایران, 2021)
Seed deterioration is one of the factors reducing seed viability and vigor. In order to investigate the effect of osmopriming on seed vigor enhancement and seedling enzyme activities, a factorial experiment was conducted in a completely randomized design with four replications in greenhouse of Research Institute of Forests and Rangelands, Tehran, Iran in 2015. Experimental factors were four sainfoin species as (Onobrichis cristagalli, O. micoxchi, O. sintensii and O. vicifolia), three levels of deteriorated seeds using accelerated ageing techniques (40°C, 98% of RH for 48 and 72h and control) and three priming treatments including hydropriming (control) and osmopriming (PEG -0.6Mpa and -1.2 Mpa). Data were collected for germination percent, rate of germination, root length, shoot length, vigor index, seedling weight and the variability in the activities of three antioxidant enzymes as superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD). Results showed that seed deterioration decreased germination traits in all of sainfoin species. Priming by seed aging interaction effect was significant for most of traits. The O.vicifolia had higher mean values for germination traits in deteriorated seeds. The result indicated that application of PEG (-0.6Mpa and -1.2 Mpa) had improved seedling growth as root and shoot length in all of the species. Measurement of enzymatic activity showed that the activities of antioxidant enzymes were decreasing in aged seeds of sainfoin. However, application of PEG (-0.6Mpa) had improved enzymatic activity in aged seeds. It was concluded that osmopriming may enhance seed vigor, seedling growth and enzyme activities in deteriorated seed of sainfoin